Art-tourism space in Łódź: the example of the Urban Forms Gallery - Mokras-Grabowska, Justyna (Turyzm/Tourism, 2021)
Łódź, as a city of huge post-industrial and modern art potential, has become in recent years a unique Polish tourism destination whose urban fabric constitutes a perfect background for street art. Examples are the murals of the Urban Forms Gallery (large format artworks) which contribute to revitalisation as well as the creation of new tourism assets to form a new tourism space: art-tourism space. The paper describes both the process of creating this space as well as its distinctive features.